Question not found

Not a good answer? Get an answer now. (Free)

Rating

There are no new answers.

Factor this expression completely, and, then, place the factors in the proper location on the grid. Place the binomial factor first.
x^3 + y^3 **Weegy:** The factored form of x^3 + y^3
is (x+y)(x^2-xy+y^2) (More)

Question

Expert Answered

Asked 3/26/2013 7:17:12 AM

0 Answers/Comments

Factor completely.
x^3 + 6x^2 - 4x - 24
a(x+ 6)(x- 2)(x+ 2)
b(x+ 2)(x- 6)(x+ 2)
c(x- 6)(x+ 2)(x+ 2) **Weegy:** 3. (x + 2)(x - 6)(x + 2) **User:** Factor completely.
-2k - k^3 - 3k^2
a k(-k+ 1)(k- 2)
b -k(k- 1)(k- 2)
c -k(k+ 1)(k+ 2) (More)

Question

Not Answered

Updated 5/31/2014 11:56:23 AM

2 Answers/Comments

x^3 + 6x^2 - 4x - 24 = (x + 6)(x - 2)(x + 2)

Added 5/31/2014 11:55:59 AM

This answer has been confirmed as correct, not copied, and helpful.

-2k - k^3 - 3k^2 = -k(k + 1)(k + 2)

Added 5/31/2014 11:56:23 AM

This answer has been confirmed as correct, not copied, and helpful.

Factor this expression completely, and, then, place the factors in the proper location on the grid. Place the binomial factor first.
a^3 - 1
**Weegy:** x^3-1
= (x-1)(x^2+x+1) **User:** Factor this expression completely, and, then, place the factors in the proper location on the grid. Place the binomial factor first.
x^3 + y^3 **Weegy:** The answer is (x+y) (x^2-x y+y^2). (More)

Question

Expert Answered

Asked 3/26/2013 7:09:50 AM

0 Answers/Comments

What is the value of "c" in the quadratic equation 3x 2 + 5x + 7 = 0?
3
5
7 **Weegy:** 2(2x/3 + 7) - 3 = 5x 4x/3 + 14 - 3 = 5x 11 = 11x/3 x = 3 y = 2(3)/3 + 7 = 9 x(y) = 3(9) = 18. Answer is d. **User:** Write the equation 2x 2 - 4x + 6 = 1 in general form and then choose the value of "c."
5
3
2.5 **Weegy:** x = 93/29 in the equation: 4(3x + 6) - 6(4x - 7) = 11x + 3(2x - 9). **User:** Write the equation 0.3x 2 + 5x - 7 = 0 in general form and then choose the value of "b."
70
50
5 **Weegy:** x=o **User:** Write the quadratic equation in general form.
(x - 3) 2 = 0
a) x2+ 9 = 0
b) x2+ 6x+ 9 = 0
c) x2- 6x+ 9 = 0 **User:** Choose the equation that best represents the general form of the following expression.
-x2+ 14x + 0
x2+ 14x= 0
x2- 14x= 0
x2- 7x+ 2 = 0 **Weegy:** x= 3/2 (More)

Question

Updated 5/28/2014 8:34:23 PM

5 Answers/Comments

The value of "c" in the quadratic equation 3x^2 + 5x + 7 = 0 is 7.

Added 5/28/2014 8:29:15 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [5/28/2014 8:31:03 PM]

The equation 2x^2 - 4x + 6 = 1 in general form is 2x^2 - 4x + 5 = 0, and we can tell the value of c is 5.

Added 5/28/2014 8:30:09 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by yumdrea [5/28/2014 8:36:09 PM]

The equation 0.3x^2 + 5x - 7 = 0 in general form is 3x^2 + 50x - 70 = 0, and we can tell the value of "b" is 50.

Added 5/28/2014 8:32:03 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by jeifunk [5/28/2014 8:45:55 PM]

What is a divided government? **Weegy:** Sir/Madam, The word devide means: to separate into two or more parts, areas, or groups. (More)

Question

Updated 9/2/2014 3:59:54 AM

1 Answer/Comment

A divided government, is one in which the executive authority is vested in a member of a party not in control of the legislative branch.

Added 9/2/2014 3:59:52 AM

This answer has been confirmed as correct, not copied, and helpful.

22,427,425 questions answered

There are no comments.